Size ratio as a predictor of recanalization in anterior communicating artery aneurysms post-endovascular treatment - Zheng, Yong; Liu, Dongtao; Ma, Xiangke; Gao, Yue; Zhou, Yang; Jia, Weihua (Interdisciplinary neurosurgery : Advanced techniques and case management, 2025)
Many studies have found that some morphological parameters of aneurysms, such as the size ratio (SR), were associated with ruptured aneurysm. However, few studies have confirmed the relationship between aneurysm parameters and recurrence after endovascular treatment (EVT). This study aimed to determine the risk factors for recurrence of anterior communicating artery aneurysm (ACoAA), the clinical outcomes, and perioperative complications following endovascular treatment. We retrospectively analyzed data from patients with ACoAA treated with EVT, including both ruptured and unruptured aneurysms. Morphological characteristics of the aneurysms and the diameter of their parent vessels were evaluated utilizing two and three-dimensional digital subtraction angiography (DSA), which included Height, Dome width, Maximum height, Neck width, Parent artery diameter, Dome-to-neck ratio, and SR. Clinical and angiographic data were collected at baseline and follow-up. A total of 51 patients were included, including 24 coil embolization patients, 18 stent assisted coil embolization (SAC) patients, and 9 balloon assisted coil (BAC) embolization patients. The median follow-up time was 9.6 months, with a major recanalization rate of 6.4 % (3 out of 47 cases). No adverse events occurred in the 3 patients with major recanalization after retreatment. Multivariate analysis showed that SR was an independent risk factor for aneurysm recanalization (OR, 7.236; 95 % CI, 1.770–29.587; p = 0.006). Good clinical outcomes were observed in 44 patients (86.3 %). High Hunt and Hess grade on admission was significantly associated with poor outcomes (OR, 11.609; 95 % CI, 1.677–80.365; p = 0.013). 6 (11.8 %) patients experienced perioperative complications. SR is a reliable morphological parameter for predicting recanalization risk of ACoAA after EVT. Given the increased risk of rebleeding and the low risk of retreatment, patients with major recanalization should undergo additional treatment.